“We’ve Tried to Keep the Beast on a Leash”: The Domestication of Digital Classroom Surveillance - Selwyn, Neil; Cumbo, Bronwyn (Surveillance & Society, 2024)
Students’ laptops are subject to growing digital forms of surveillance by their schools. Following the theoretical tradition of media “domestication,” this paper examines the incorporation of Student Activity Monitoring Software (SAMS) into the everyday routines of one Australian secondary school. Drawing on two years of fieldwork, the paper details how SAMS was broadly accepted by school staff and students as complementing—rather than challenging—the moral economy of the school. With school leaders keen to increase student surveillance without being seen to diminish teacher professionalism, the paper shows how SAMS was appropriated and objectified in ways that teachers and students perceived as preserving established classroom power relations. At the same time, school leaders could maintain core school values while also projecting an appearance of innovation and being “data-driven.” However, rather than this surveillance system being wholly “tamed,” we also show how SAMS was leading to subtle shifts within the school—not least the surrendering of governance and accountability to the software company, alongside the further entrenchment of “soft surveillance” logics into classrooms.